Temperature-dependent transformation and solubility of trace metals in palm kernel shell ash - Satoshi Takeuchi; Kosei Yamashita; Yohey Hashimoto (Biomass and Bioenergy, 2026)

Environmental Exosomes/Small Extracellular Vesicles: Evidence of Extracellular RNA Release by Aquatic Organisms - Ryo Yonezawa; Lingxin Meng; Naoki Hashimoto; Ibuki Igarashi; Satoshi Kimura; Nina Yasuda; Susumu Mitsuyama; Takanori Kobayashi; Kazutoshi Yoshitake; Shigeharu Kinoshita; Nahoko Bailey-Kobayashi; Kaoru Maeyama; et al. (Marine Biotechnology, 2026)

Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

The Ancestor and Evolution of the Giant Muscle Protein Connectin/Titin - Akira Hanashima; Yuu Usui; Ken Hashimoto; Satoshi Mohri (Journal of Molecular Evolution, 2025)
The emergence of connectin, also called titin, a muscular spring and the largest protein in living organisms, is critical in metazoan evolution as it enables striated muscle-based locomotion. However, its evolutionary history remains unclear. Here, we investigated the evolutionary process using genomic analysis and deduced the ancestor of connectin. The region between the HOX and WNT clusters in the human genome, where the connectin gene ( CON ( TTN )) is located, was quadrupled by two rounds of whole-genome duplication (WGD) in the ancestor of jawed vertebrates. However, connectin ohnologs were deleted before the advent of jawed vertebrates, resulting in a single connectin gene. Additionally, one of the connectin ohnologs created by the third round of teleost WGD disappeared, while the other was duplicated on the same chromosome. We also discovered that the connectin and connectin family genes consistently underwent local duplication on the same chromosome, though the underlying mechanism remains unknown. Using synteny analysis, we identified KALRN and its ohnolog TRIO as putative ancestral paralogs of the connectin gene. TRIO/KALRN has a connected structure of SESTD1 - CCDC141 - CON ( TTN ), and its synteny is conserved in the Drosophila genome. Furthermore, we confirmed that this connected structure, termed ‘connectitin,’ (connected-connectin/titin) is conserved in cnidarians and placozoans. Molecular phylogenetic analysis revealed that it diverged from TRIO/KALRN prior to the emergence of these animals, suggesting that metazoan muscle may have a single origin. These findings enhance our understanding of the evolutionary processes of striated muscles in the animal kingdom.

Trauma-Induced Phaeohyphomycosis Caused by Cladosporium crousii Presenting as a Punched-Out Ulcer - Shota Itagaki; Hiromitsu Noguchi; Masataro Hiruma; Takashi Yaguchi; Yoshihiro Satoh; Satoshi Okuno; Takashi Hashimoto; Takahiro Satoh (Mycopathologia, 2025)

Helicovermis profundi gen. nov., sp. nov., a novel mesophilic, asporogenous bacterium within the Clostridia isolated from a deep-sea hydrothermal vent chimney - Urara Miyazaki; Daiki Mizutani; Yurina Hashimoto; Akihiro Tame; Shigeki Sawayama; Junichi Miyazaki; Ken Takai; Satoshi Nakagawa (Antonie van Leeuwenhoek, 2024)

Cross-hierarchical analysis of self-assembly dynamics in enzyme-treated rice gel during retrogradation - Nakako Katsuno; Misa Onishi; Takumi Taguchi; Chie Ohmoto; Hideyuki Yamaguchi; Takuya Hashimoto; Satoshi Iwamoto; Teppei Imaizumi; Takahisa Nishizu (Food Hydrocolloids, 2024)

Nucleophagy in Aspergillus oryzae is Mediated by Autophagosome Formation and Vacuole-Mediated Degradation - Mau Hashimoto; Satoshi Kimura; Manabu Arioka (Current Microbiology, 2024)
We previously reported autophagy-mediated degradation of nuclei, nucleophagy, in the filamentous fungus Aspergillus oryzae . In this study, we examined whether nuclei are degraded as a whole. We generated A. oryzae mutants deleted for orthologs of Saccharomyces cerevisiae YPT7 and ATG15 which are required, respectively, for autophagosome-vacuole fusion and vacuolar degradation of autophagic bodies. Degradation of histone H2B-EGFP under starvation conditions was greatly decreased in the Δ Aoypt7 and Δ Aoatg15 mutants. Fluorescence and electron microscopic observations showed that autophagosomes and autophagic bodies surrounding the entire nuclei were accumulated in the cytoplasm of Δ Aoypt7 and the vacuole of Δ Aoatg15 , respectively. These results indicate that nuclei are engulfed in the autophagosomes as a whole and transported/released into the vacuolar lumen where they are degraded.

Anti-biofouling performance and microbial communities of an integrated fixed-film activated sludge membrane bioreactor with a fibrous carrier material: Pilot-scale demonstration - Hiroyuki Yoshino; Hop Van Phan; Naomichi Mori; Naoki Ohkuma; Masaki Kawakami; Masahiko Nihei; Satoshi Hashimoto; Ken Wakabayashi; Tomoyuki Hori; Akihiko Terada (Science of The Total Environment, 2024)

Time-of-flight magnetic resonance angiography for detection of postoperative recurrence in patients with chronic subdural hematoma - Kimitoshi Sato; Go Horiguchi; Satoshi Teramukai; Takashi Yoshida; Fuminori Shimizu; Naoya Hashimoto (Acta Neurologica Belgica, 2023)

Estimating relative gear efficiency of surface trawl nets using comparative trawl survey data - Shin-Ichiro Nakayama; Satoshi Suyama; Taiki Fuji; Midori Hashimoto (Fisheries Science, 2023)

Exploring the Spatial Pattern of Urban Forest Ecosystem Services based on i-Tree Eco and Spatial Interpolation: A Case Study of Kyoto City, Japan - Yusong Xie; Satoshi Hirabayashi; Shizuka Hashimoto; Shozo Shibata; Jiefeng Kang (Environmental Management, 2023)

Advanced spawning in Pacific bluefin tuna, Thunnus orientalis, by a shift in consecutive photothermal regimes in a land-based tank - Kentaro Higuchi; Satoshi Soma; Toshinori Takashi; Keita Ishii; Takeshi Eba; Hiroshi Hashimoto; Taizo Morioka; Kazunori Kumon; Kogen Okita; Takao Hayashida; Sho Hosoya; Koichiro Gen (Aquaculture, 2023)

Brain 5-HT2A receptor binding and its neural network related to behavioral inhibition system - Kazuho Kojima; Shigeki Hirano; Yasuyuki Kimura; Chie Seki; Yoko Ikoma; Keisuke Takahata; Takehito Ito; Keita Yokokawa; Hiroki Hashimoto; Kazunori Kawamura; Ming-Rong Zhang; Hiroshi Ito; et al. (Brain Imaging and Behavior, 2022)
The tendency to avoid punishment, called behavioral inhibition system, is an essential aspect of motivational behavior. Behavioral inhibition system is related to negative affect, such as anxiety, depression and pain, but its neural basis has not yet been clarified. To clarify the association between individual variations in behavioral inhibition system and brain 5-HT 2A receptor availability and specify which brain networks were involved in healthy male subjects, using [ 18 F]altanserin positron emission tomography and resting-state functional magnetic resonance imaging. Behavioral inhibition system score negatively correlated with 5-HT 2A receptor availability in anterior cingulate cortex. A statistical model indicated that the behavioral inhibition system score was associated with 5-HT 2A receptor availability, which was mediated by the functional connectivity between anterior cingulate cortex and left middle frontal gyrus, both of which involved in the cognitive control of negative information processing. Individuals with high behavioral inhibition system displays low 5-HT 2A receptor availability in anterior cingulate cortex and this cognitive control network links with prefrontal-cingulate integrity. These findings have implications for underlying the serotonergic basis of physiologies in aversion.

Reduced body weight of Pacific saury ( Cololabis saira ) causes delayed initiation of spawning migration - Shigeho Kakehi; Midori Hashimoto; Miyako Naya; Shin‐ichi Ito; Hiroomi Miyamoto; Satoshi Suyama (Fisheries Oceanography, 2022)
The fishing grounds of the Pacific saury began shifting eastward after 2013 and deviated further east in 2019 and 2020. Consequently, the migration pattern from the pre‐fishing distribution to fishing grounds may be changing. This study investigated inter‐annual variations in westward spawning migration parameters using a migration model. Case studies were conducted to estimate optimal values for the initiation date of spawning migration and migration speed during spawning migration. The estimated optimal initiation date of spawning migration from 2003 to 2018 was July 13 to August 8, with an average of July 31. However, in 2019 and 2020, the initiation date of spawning migration was August 22 and September 5, respectively, significantly later than that in 2003–2018 ( p p > .7). These results indicate that delays in the initiation of spawning migration occurred in 2019 and 2020, leading to an eastward shift of fishing grounds. The mean body weight of the age‐1 Pacific saury in the pre‐fishing season had a significant negative correlation ( p p

Correction to: Comparison of biomass estimates from multiple stratification approaches in a swept area method for Pacific saury Cololabis saira in the western North Pacific - Midori Hashimoto; Hideaki Kidokoro; Satoshi Suyama; Taiki Fuji; Hiroomi Miyamoto; Miyako Naya; Dharmamony Vijai; Yasuhiro Ueno; Toshihide Kitakado (Fisheries Science, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s12562-021-01506-9

A multi-actor and bottom-up perspective on attaining rural water security: qualitative evidence from India - Mrittika Basu; Rajarshi DasGupta; Shizuka Hashimoto; Satoshi Hoshino (Environment, Development and Sustainability, 2021)

A familial cluster of severe coronavirus disease 2019 that required intubation of all family members - Takashi Katsuno; Manabu Suzuki; Masahiro Ishikane; Noriko Kinoshita; Akinari Tsukada; Chie Morita; Yusaku Kusaba; Keita Sakamoto; Yoh Yamaguchi; Yoshie Tsujimoto; Masao Hashimoto; Junko Terada; et al. (Infectious Diseases, 2020)

Scaffold attachment factor B: distribution and interaction with ERα in the rat brain - Takashi Hashimoto; Mitsuhiro Kawata; Yukie Hirahara; Mayumi Nishi; Iino Satoshi; Ken-Ichi Matsuda (Histochemistry and Cell Biology, 2020)

Comparison of biomass estimates from multiple stratification approaches in a swept area method for Pacific saury Cololabis saira in the western North Pacific - Midori Hashimoto; Hideaki Kidokoro; Satoshi Suyama; Taiki Fuji; Hiroomi Miyamoto; Miyako Naya; Dharmamony Vijai; Yasuhiro Ueno; Toshihide Kitakado (Fisheries Science, 2020)
Fishery-independent surveys using sea surface trawl nets for Pacific saury Cololabis saira in the western North Pacific since 2003 have enabled the investigation of their annual distribution patterns and total biomass during June and July, prior to the main fishing season in Japan. We compared biomass estimates and their associated variances derived based on five different post-stratification approaches in a swept area method, and then observed that these approaches have little effect on biomass estimates and their precision, owing to well-organized survey designs and homogeneously allocated sampling stations. We were able to utilize decreasing biomass estimates for 15 years as an essential abundance index in the ongoing stock assessment. Notably, examination based on stratification along with longitudinal survey lines indicated that the estimated biomass had decreased in the western survey area, resulting in an eastward shift in the gravity center of Pacific saury distribution after 2010. We recommend biomass estimation in an east–west direction based on longitudinal stratification as an effective measure to develop population dynamics models which reflect westward migration into the fishing grounds around Japanese coastal waters, and to forecast the expected catch during the subsequent fishing period.

A pragmatic analysis of water supply and demand, and adaptive capacity in rural areas: development of Rural Water Insecurity Index - Mrittika Basu; Satoshi Hoshino; Shizuka Hashimoto (Natural Hazards, 2016)

Neuropeptide W-Induced Hypophagia is Mediated Through Corticotropin-Releasing Hormone-Containing Neurons - Fumiko Takenoya; Lihua Wang; Haruaki Kageyama; Satoshi Hirako; Nobuhiro Wada; Hirofumi Hashimoto; Yoichi Ueta; Junichi Sakagami; Naoko Nonaka; Seiji Shioda (Journal of Molecular Neuroscience, 2015)

New buoy observation system for tsunami and crustal deformation - Narumi Takahashi; Yasuhisa Ishihara; Hiroshi Ochi; Tatsuya Fukuda; Jun’ichiro Tahara; Yosaku Maeda; Motoyuki Kido; Yusaku Ohta; Katsuhiko Mutoh; Gosei Hashimoto; Satoshi Kogure; Yoshiyuki Kaneda (Marine Geophysical Research, 2014)

Generation of gene-targeted mice using embryonic stem cells derived from a transgenic mouse model of Alzheimer’s disease - Satoshi Yamamoto; Yuki Ooshima; Mitsugu Nakata; Takashi Yano; Kunio Matsuoka; Sayuri Watanabe; Ryouta Maeda; Hideki Takahashi; Michiyasu Takeyama; Yoshio Matsumoto; Tadatoshi Hashimoto (Transgenic Research, 2013)

Plasmid-mediated bioaugmentation of sequencing batch reactors for enhancement of 2,4-dichlorophenoxyacetic acid removal in wastewater using plasmid pJP4 - Hirofumi Tsutsui; Yasutaka Anami; Masami Matsuda; Kurumi Hashimoto; Daisuke Inoue; Kazunari Sei; Satoshi Soda; Michihiko Ike (Biodegradation, 2013)

Food exchange behavior between multiple founding queens of Polyrhachis moesta (Hymenoptera: Formicidae) changes during hibernation - Ayano Hashimoto; Ken Sasaki; Satoshi Koyama; Toshiyuki Satoh (Applied Entomology and Zoology, 2013)

Derivation of rat embryonic stem cells and generation of protease-activated receptor-2 knockout rats - Satoshi Yamamoto; Mitsugu Nakata; Reiko Sasada; Yuki Ooshima; Takashi Yano; Tadahiro Shinozawa; Yasuhiro Tsukimi; Michiyasu Takeyama; Yoshio Matsumoto; Tadatoshi Hashimoto (Transgenic Research, 2012)

In vitro antitrypanosomal activity of some phenolic compounds from propolis and lactones from Fijian Kawa (Piper methysticum) - Kazuhiko Otoguro; Masato Iwatsuki; Aki Ishiyama; Miyuki Namatame; Aki Nishihara-Tsukashima; Hiroaki Kiyohara; Toshihiro Hashimoto; Yoshinori Asakawa; Satoshi Ōmura; Haruki Yamada (Journal of Natural Medicines, 2012)

In vitro antitrypanosomal activity of bis(bibenzyls)s and bibenzyls from liverworts against Trypanosoma brucei - Kazuhiko Otoguro; Aki Ishiyama; Masato Iwatsuki; Miyuki Namatame; Aki Nishihara-Tukashima; Hiroaki Kiyohara; Toshihiro Hashimoto; Yoshinori Asakawa; Satoshi Ōmura; Haruki Yamada (Journal of Natural Medicines, 2012)

Photosensitivity in mice caused by pyropheophorbide in the midgut gland of the scallop Patinopecten yessoensis observed in diarrhetic shellfish poisoning mouse bioassays - Satoshi Hashimoto; Kenichi Ueno; Kenichi Takahashi; Toshiyuki Suzuki; Yutaka Itabashi (Fisheries Science, 2010)

Complete nucleotide sequence and genome organization of butterbur mosaic virus - Masayoshi Hashimoto; Ken Komatsu; Kensaku Maejima; Yasuyuki Yamaji; Yukari Okano; Takuya Shiraishi; Shuichiro Takahashi; Satoshi Kagiwada; Shigetou Namba (Archives of Virology, 2009)

Complete nucleotide sequence of a California isolate of Radish mosaic virus - Ken Komatsu; Kouji Hatada; Masayoshi Hashimoto; Johji Ozeki; Kensaku Maejima; Satoshi Kagiwada; Yasuyuki Yamaji; Shigetou Namba (Archives of Virology, 2008)

Establishment and characterization of a human cell line derived from a uterine papillary serous carcinoma with wild-type p53 function - Hisashi HASHIMOTO; Atsumi KOJIMA; Tamotsu SUDO; Noriyoshi OHKI; Satoshi YAMAGUCHI; Yoshiki MIKAMI; Masaharu ITO; Ryuichiro NISHIMURA (Human Cell, 2008)

Evaluation of three phytoplankton species as food for the pearl oyster Pinctada fucata - Tomoki Hashimoto; Katsuya Hyodoh; Takuma Hirose; Satoshi Nishikawa; Toshiya Katano; Shin-ichi Nakano (Aquaculture International, 2008)

Establishment and characterization of a cell line (BTIC) including HER-2-positive cells derived from pleural effusion of recurrent breast invasive ductal carcinoma, scirrhous type - Kouzou NINOMIYA; Satoshi OHI; Isao TABEI; Song JIN; Toshiaki TACHIBANA; Shigeo YAMASHITA; Katsuhiko YANAGA; Hisashi HASHIMOTO (Human Cell, 2007)

Establishment and characterization of an IGSK-2 cell line derived from ascitic fluid of recurrent hCG and somatostatin secreted adenocarcinoma of the stomach - Satoshi OHI; Naoto TAKAHASHI; Hisashi HASHIMOTO; Toshiaki TACHIBANA; Tetsuya HIRABAYASHI; Kayoko SUGIYAMA; Katsuhiko YANAGA; Hiroshi ISHIKAWA (Human Cell, 2007)

Establishment and characterization of a cisplatin-resistant cell line (IGSK-1) from a poorly differentiated gastric adenocarcinoma - Satoshi OHI; Naoto TAKAHASHI; Kouzou NINOMIYA; Masako NAKAJIMA; Hisashi HASHIMOTO; Toshiaki TACHIBANA; Katsuhiko YANAGA; Hiroshi ISHIKAWA (Human Cell, 2007)

Establishment and characterization of a cell line (NABCA) derived from metastatic lymph nodes of breast scirrhous carcinoma - Satoshi OHI; Shigeya KYODA; Isao TABEI; Kouzou NINOMIYA; Kayoko SUGIYAMA; Hisashi HASHIMOTO; Toshiaki TACHIBANA; Hiroshi ISHIKAWA (Human Cell, 2006)

New skin-equivalent model from de-epithelialized amnion membrane - Lujun Yang; Yuji Shirakata; Masachika Shudou; Xiuju Dai; Sho Tokumaru; Satoshi Hirakawa; Koji Sayama; Junji Hamuro; Koji Hashimoto (Cell and Tissue Research, 2006)

cDNA cloning of Japanese oyster stress protein homologous to the mammalian 78-kDa glucose regulated protein and its induction by heatshock - Yoshihiro YOKOYAMA; Hisashi HASHIMOTO; Satoshi KUBOTA; Akira KURIYAMA; Yoichi OGURA; Shoshi MIZUTA; Reiji YOSHINAKA; Haruhiko TOYOHARA (Fisheries Science, 2006)

Expression of endothelial nitric oxide synthase is suppressed in the renal vasculature of angiotensinogen-gene knockout mice - Minoru Kihara; Keiko Sato; Tatsuo Hashimoto; Nozomi Imai; Yoshiyuki Toya; Satoshi Umemura (Cell and Tissue Research, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Expression of HSP70 in response to heat-shock and its cDNA cloning from Mediterranean blue mussel - Haruhiko TOYOHARA; Masatomi HOSOI; Isao HAYASHI; Satoshi KUBOTA; Hisashi HASHIMOTO; Yoshihiro YOKOYAMA (Fisheries Science, 2005)

Molecular analysis of congenital central hypoventilation syndrome - Ayako Sasaki; Masayo Kanai; Kazuki Kijima; Kazuhiro Akaba; Motoya Hashimoto; Hisaya Hasegawa; Shinsuke Otaki; Takenobu Koizumi; Satoshi Kusuda; Youhei Ogawa; Keiji Tuchiya; Wakako Yamamoto; et al. (Human Genetics, 2003)

Real-time [ 11 C]methionine translocation in barley in relation to mugineic acid phytosiderophore biosynthesis - Naimatullah Bughio; Hiromi Nakanishi; Shoichiro Kiyomiya; Shinpei Matsuhashi; Noriko-Shigeta Ishioka; Satoshi Watanabe; Hiroshi Uchida; Atsunori Tsuji; Tamikazu Kume; Shoji Hashimoto; Toshiaki Sekine; Akihiko Osa; et al. (Planta, 2001)

Physiological Modeling of Altered Pharmacokinetics of a Novel Anticancer Drug, UCN-01 (7-Hydroxystaurosporine), Caused by Slow Dissociation of UCN-01 from Human α1-Acid Glycoprotein - Eiichi Fuse; Akitoshi Hashimoto; Natsuko Sato; Hiromi Tanii; Takashi Kuwabara; Satoshi Kobayashi; Yuichi Sugiyama (Pharmaceutical Research, 2000)

Transfer and distribution of accumulated (14C)polychlorinated biphenyls from maternal to fetal and suckling rats - Yasuhiro Takagi; Satoshi Aburada; Kazuo Hashimoto; Toshiyuki Kitaura (Archives of Environmental Contamination and Toxicology, 1986)